2011
DOI: 10.1055/s-0031-1297071
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Praziquantel and Ro 15-5458, a 9-Acridanone-hydrazone Derivative, against Schistosoma haematobium

Abstract: The efficacy of Ro 15-5458 ([10-(2-diethylamino)ethyl)-9-acridanone(thiazolidin-2-ylidene)hydrazone, CAS 92928-47-7) as a new antischistosomal drug was studied in hamsters using a dose of 20 mg/kg body weight against an Egyptian strain of Schistosoma haematobium, in comparison with praziquantel (PZQ, CAS 55268-74-1) (full dose 1000 mg/kg body weight). This was carried out at 4, 8 and 12 weeks post cercarial exposure of hamsters. The criteria used for the assessment of drug efficacy were the worm load, oogram p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The reduction of eggs/ gram liver and intestine was higher in the group treated with Ro 15-5458, being 95.7% and 98.2%, compared to 65.3% and 79.2% in the praziquantel treated group, respectively. Regarding the efficacy in older infection (at 8 and 12 weeks post-exposure), both drugs showed similar results with respect to reduction in worm load, change in oogram pattern, and reduction in the number of eggs per gram liver and intestinal tissues (Guirguis 2003). The author concluded that Ro 15-5458 had a comparable efficacy to that of praziquantel in the treatment of mature infection of S. haematobium with the additional advantage of showing better effects in immature infection.…”
Section: Ro 15-5458mentioning
confidence: 90%
See 1 more Smart Citation
“…The reduction of eggs/ gram liver and intestine was higher in the group treated with Ro 15-5458, being 95.7% and 98.2%, compared to 65.3% and 79.2% in the praziquantel treated group, respectively. Regarding the efficacy in older infection (at 8 and 12 weeks post-exposure), both drugs showed similar results with respect to reduction in worm load, change in oogram pattern, and reduction in the number of eggs per gram liver and intestinal tissues (Guirguis 2003). The author concluded that Ro 15-5458 had a comparable efficacy to that of praziquantel in the treatment of mature infection of S. haematobium with the additional advantage of showing better effects in immature infection.…”
Section: Ro 15-5458mentioning
confidence: 90%
“…These results were confirmed with the absence or minimal histopathological changes in the liver of mice 2 weeks posttreatment (Metwally et al 1997). Guirguis (2003) investigated the antischistosomal activity of Ro15-5458, in a dose of 20 mg/kg body weight in hamsters experimentally infected with Schistosoma haematobium compared to praziquantel in a full dose of 1,000 mg/kg body weight. In this study, Ro15-5458 proved to be more efficacious than praziquantel in earlier stages of infection (4 weeks post-cercarial exposure) where worm load was reduced by 83.2% and 55.6%, respectively, compared to the infected untreated control.…”
Section: Ro 15-5458mentioning
confidence: 99%
“…Moreover, Martins-Leite et al (2008) concluded that the chemotherapy with PZQ is effective in reducing the morbidity of the disease. Guirguis (2012) reported that reduction in the egg tissue count of infected host after PZQ treatment could be through hindering the process of oviposition. The percent reduction in the egg count was found to be higher in the intestinal tissue than in the hepatic tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The death of the worms due to the treatment with antischistosomal drugs was attributed to metabolic disorders, mechanical destruction and muscular contraction of the treated worms (Doenhoff et al, 2002). The parasitological improvement is due to antiparasitic drug PZQ which causes direct or indirect toxic effect in combination with the effect of immunization with SEA which lead marked decrease in the worm number or fecundity due to hindering the process of oviposition (Guirguis, 2003).…”
Section: Discussionmentioning
confidence: 99%